The Effect of Some Coating Materials on the amount of Leaching Monomer from Poly Methyl Methacrylate Denture Base - Nadia T Jaffer; Monia MN Kandil (University of Mosul, College of Dentistry, 2009)
Aims: to evaluate the effect of three coating materials on the amount of residual monomer leaching fromacrylic resin denture base. Materials and methods: twenty specimens of a heat-cured acrylic resin denturebase were prepared at dimensions of 30 x 10 x 1.5 mm length, width and thickness; respectively. Thesespecimens were divided into four groups: control (in which the denture base left uncoated), monopolycoated, grape seeds oil coated and olive oil coated groups. For monomer leaching analysis, each specimenwas put in a glass tube containing 10 ml of deionized water that was changed daily. Monomer levels weremeasured by spectrophotometer at 254 nm, every 24 hour for 7 days analytic period. The results were expressedas a percentage of leached monomer mass with respect to the weight of specimen. Results: statisticalanalysis showed that there was a significant difference in the percentage of residual monomer leachingin uncoated and monopoly coated groups; and insignificant difference in grape and olive oils coatedgroups. However, there was a daily decrease in monomer leaching for all groups. Grape and olive oilscoated groups, showed lower leached residual monomer during the whole experimental period than theuncoated and monopoly coated specimens, the daily reduction of monomer leaching was sharp in the uncoated(control) and monopoly coated groups, and it was gradual and slow in oils coated groups. Conclusions:the using of natural oils (grape and olive oils), was more beneficial in reduction of residual monomerleaching, than the resin coating materials (monopoly) in comparison to uncoated acrylic resin denture base.Key words: Acrylic resin denture base, monomer leaching, coating materials, monopoly, natural oils.